Evaluation of Management Information Systems for Pharmaceutical Inventory Control at The Hospital - Diah Kartika Putri; Jason Merari Peranginangin; Prasojo Pribadi (Universitas Aisyah Pringsewu, 2022)
Hospital X is one of the hospitals in Lampung that has implemented management information systems for pharmacy since 2016, has not yet been evaluated, and there are several obstacles, such as the absence of warnings for out-of-stock drugs and drug procurement planning is still calculated manually. This research was a descriptive study with a cross-sectional approach to the management information system of pharmaceutical inventory control. This research data comes from the distribution of the DeLone and McLean questionnaires and the results of structured interviews to support system development. Based on calculations using a predetermined formula, it is said that the level of respondents' satisfaction with management information systems drug inventory control is in the medium category, but is still very far from the high satisfaction category, so further interviews are needed. After developing a pharmaceutical inventory control management information system, there were 18 participants from the pharmacy participated in training and self-testing for eight days. Based on the research that has been done, it can be concluded that the level of the respondent's satisfaction category has increased its variables, the satisfaction variable has a perception of satisfaction in the medium category of 100% and the high category of 0%, but after developing a pharmaceutical inventory control system, the satisfaction level of respondents in the high category has increased was 27.78%, so the development of a control management information system needs to be done. Abstrak: Rumah sakit X salah satu rumah sakit di Lampung yang sudah menerapkan SIM farmasi sejak tahun 2016, hingga saat ini belum dilakukan evaluasi, dan terdapat beberapa kendala seperti, belum adanya peringatan untuk stok obat yang habis dan perencanaan pengadaan obat masih dihitung secara manual. Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross sectional pada sistem informasi manajemen pengendalian persediaan farmasi. Data penelitian ini berasal dari hasil pendistribusian kuesioner De Lone dan Mc Lean serta hasil wawancara terstrukur untuk mendukung pengembangan sistem. Berdasarkan perhitungan menggunakan rumus yang telah ditentukan dikatakan bahwa tingkat kepuasan responden terhadap SIM pengendalian persediaan obat dalam kategori sedang, namun masih sangat jauh dari kategori kepuasan tinggi, sehingga perlu dilakukan wawancara lebih lanjut. Setelah dilakukan pengembangan SIM pengendalian persediaan farmasi kemudian dilakukan pelatihan yang diikiuti oleh 18 peserta dari farmasi dan uji coba mandiri selama delapan hari. Berdasarkan penelitian yang telah dilakukan dapat disimpulkan bahwa tingkat kategori kepuasan responden mengalami peningkatan pervariabelnya, pada variabel kepuasan memiliki persepsi kepuasan dalan kategori sedang sebesar 100% dan kategori tinggi 0%, namun setelah dilakukan pengembangan sistem pengendalian persediaan farmasi tingkat kepuasan responden pada kategori tinggi mengalami peningkatan sebesar 27,78%, sehingga pengembangan sistem informasi manajemen pengerdalian perlu dilakukan.